Retroperitoneal laparoscopic adrenalectomy for large adrenal tumors—analysis of tumor size and adverse events: a retrospective single-center study - Tsai, I-Chen; Hsieh, Yu-Che; Tseng, Wen-Hsin; Liu, Chien-Liang; Ho, Chung-Han; Li, Chien-Feng; Chiu, Allen W.; Huang, Steven K. (Frontiers in Surgery, 2024)
Adrenal tumors are relatively common, and adrenalectomy is the third most common endocrine surgery. Patients with adrenal tumors were categorized into two groups for analysis: those with intermediate (4-6 cm, Group 1) and large (>6 cm, Group 2) tumors undergoing Retroperitoneal Laparoscopic Adrenalectomy (RLA). The primary outcome is to compare the surgical outcomes between these two groups. The secondary outcome involves analyzing the relationship between tumor characteristics and the incidence of adverse events. Data from 76 patients who underwent RLA for tumors of size ≥4 cm between 2005 and 2022 at a single tertiary referral center were analyzed retrospectively. Variables, including patients’ age, hormone function, operation time, conversion to open approach, perioperative complications, and adverse surgical events (blood loss >500cc, conversion to open approach, and perioperative complications), were assessed. No significant differences were observed between the two groups in terms of functional and histopathologic analysis, gender distribution, functioning factors, perioperative complications, and estimated blood loss. However, patients in Group 2 were younger (median age 50, IQR:40-57, P=0.04), experienced longer operative times (median 175 mins, IQR:145-230 mins, P=0.005), and had a higher rate of conversion to open surgery (12%, P=0.033). For every 1 cm increase in tumor size, the odds ratio for adverse surgical events increased by 1.58. In conclusions, RLA is a safe and feasible procedure for adrenal tumors larger than 6 cm. While intraoperative and postoperative complications are not significantly increased in either group, larger tumors increase surgery times and are more likely to require conversion to open surgery. Therefore, caution and preparedness for potential adverse events are recommended when dealing with larger tumors. A tumor size of 5.3 cm may serve as a guide for risk stratification and surgical planning in large adrenal tumor management.